A multi-criteria decision model for the selection of professional service innovative organisation. (2017) - Soni, Gunjan; Vinayak, Kalluri; Tyagi, Aditya
The purpose of this paper is to demonstrate an application of a multi-criteria decision model (MCDM) for the selection of best professional service organisation (PSO) from a number of available alternatives based on service innovation elements. For that purpose, a conceptual model for MCDM has been adopted. Different service innovation elements are classified into critical, objective and subjective factors in the evaluation process and the selection procedure is demonstrated with a hypothetical case. The decision to select a particular professional service organisation is very important when multiple professional service organisations are available. A quantitative basis for comparison and selection of the professional service organisation among a host of alternative professional service organisation could greatly impact on the eventual organisations brand image. Thus, an algorithm - performance value analysis (PVA), for the selection of PSO has been developed from literature. The study expands the scope for managers in selecting the best professional service organisation.